2017
DOI: 10.1080/10888705.2017.1403324
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioral indices of short-term stress in wild vicuñas (Vicugna vicugna) in Jujuy Province, Argentina

Abstract: The management of wild vicuñas can trigger a stress response that may compromise welfare. In Santa Catalina, Jujuy Province, Argentina, indices of short-term stress associated with capture, handling, and shearing were studied in 105 wild vicuñas (Vicugna vicugna). The study included 2 groups (n = 59 and n = 46) of wild vicuñas captured in 2 consecutive days. Independent variables analyzed included sex, restraint time, and groups. Cortisol, creatine kinase, glucose, white blood cells, temperature, heart rate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… Gómez-Puerta et al (2022) do not report differences, by sex or age, between vicuñas affected with S. scabiei in Cuzco. Although there is no consensus on susceptibility according to sex ( Acebes et al, 2022 ), in Argentina, female vicuñas show a higher level of cortisol during the capture ( Marcoppido et al, 2018 ) and this can affect the immune response, giving greater susceptibility to scabies. Furthermore, females, unlike males, spend more time grouped together, in close contact with their offspring, and near the areas of wallowing, where we have identified the presence of mites ( Siguas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… Gómez-Puerta et al (2022) do not report differences, by sex or age, between vicuñas affected with S. scabiei in Cuzco. Although there is no consensus on susceptibility according to sex ( Acebes et al, 2022 ), in Argentina, female vicuñas show a higher level of cortisol during the capture ( Marcoppido et al, 2018 ) and this can affect the immune response, giving greater susceptibility to scabies. Furthermore, females, unlike males, spend more time grouped together, in close contact with their offspring, and near the areas of wallowing, where we have identified the presence of mites ( Siguas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that capture, handling, live-shearing and releasing wild Vicuñas under strict sustainable management and welfare protocols (although showing subtle and transitory behavioural and social structure changes after being released) does not compromise the conservation or maintenance of ecologically functional wild populations (Sahley et al 2007, Marcoppido et al 2017). Among the two widely used methods for capturing Vicuñas, the traditional 'Chaku' (surround-capture by people on foot) results in less stress on animals than the use of motor vehicles to chase the animals (Sarno et al 2009, Arzamendia et al 2010.…”
Section: C) On the Cooperation Between Exporting And Importing Countriesmentioning
confidence: 99%